Examining a Northern Sámi-Norwegian dual language picturebook in English language education through a critical translingual-transcultural lens - Nayr Correia Ibrahim (Intercultural Communication Education, 2022)
The present article explores the affordances of a dual language Northern Sámi – Norwegian picturebook in addressing multilingualism and interculturality in the primary English language classroom. Both notions of interculturality and multilingualism have received increased attention as fundamental components in English language teaching (ELT), yet they have been mostly addressed as separate concepts. Furthermore, because interculturality has traditionally been theorised as communicating across geographical/national borders, local diversities, such as indigenous cultures and languages, have often been overlooked or misrepresented in the language classroom. Similarly, linguistic diversity has mostly been viewed through the monolingual lens. As classrooms around the world have become increasingly diverse, both culturally and linguistically, it is important for teachers to engage with these multiple languages and identities, not as separate entities in faraway lands, but also through an exploration of local indigenous diversities. The dual language picturebook provides a textual-visual space to engage teachers and learners with the multilingual turn in tandem with the transcultural perspective. The chosen picturebook, Ábiid plástihkat – Plasten i havet (2020), by Rita Sørly (author) and Malgorzata Piotrowska (illustrator) opens up the interpretative possibilities of multimodal texts as socially-just, diversity-focused, visually-complex and language-conscious semiotic objects. Embedded in a specific cultural context, the English classroom in northern Norway, this paper positions the dual language picturebook as a potential resource for exploring indigenous languages and cultures in Grades 1-7 and for attending to global-local diversities through a critical translingual-transcultural lens.